KMT2A-rearranged acute lymphoblastic leukaemia - Rishi S. Kotecha; Rob Pieters; Janine Stutterheim (EJC Paediatric Oncology)
KMT2A-rearranged acute lymphoblastic leukaemia (ALL) represents a high risk subtype of childhood ALL. Historical treatment strategies have comprised of intensification with conventional chemotherapy. However, outcomes have remained consistently poor compared to the advances that have been seen for other ALL subtypes, particularly for infants diagnosed before their first birthday. The advent of novel immunotherapeutic approaches has led to a change in the treatment paradigm, with the integration of blinatumomab to the current suite of clinical trials for KMT2A-rearranged ALL expected to result in marked improvements. Furthermore, significant progress has been made to understand the unique biology of KMT2A-rearranged ALL, which has led to the development of novel agents that directly target the KMT2A complex or dysregulated proteins/pathways. Clinical trials are currently poised to evaluate therapies such as venetoclax and menin inhibitors, offering further hope for achieving a cure. In this review, we discuss the remarkable progress that has been made for KMT2A-rearranged ALL, leading to much optimism for improved outcomes in the future.